Dynamic volume‐rendered optical coherence tomography pupillometry. Issue 6 (8th November 2021) - Maloca, Peter M.; de Carvalho, Emanuel R.; Hasler, Pascal W.; Balaskas, Konstantinos; Inglin, Nadja; Petzold, Axel; Egan, Catherine; Tufail, Adnan; Scholl, Hendrik P. N.; Valmaggia, Philippe
Abstract: Purpose: To assess intrapupillary space (IPS) changes in healthy subjects with regard to decreased iris motility in patients with pseudoexfoliation glaucoma (PEXG) or non‐arteritic anterior ischaemic optic neuropathy (NAION) in a feasibility study in a clinical environment. Methods: Scotopic and photopic IPS measurements using three‐dimensionally rendered swept‐source optical coherence tomography (SS‐OCT) data were obtained and compared for all subjects. Intrapupillary space (IPS) parameters were evaluated such as absolute volumetric differences, relative light response for volumetric ratios and pupillary ejection fraction (PEF) for functional contraction measurements. Results: From a total of 122 IPS from 66 subjects, 106 IPS were eligible for comparison providing values for 72 normal, 30 PEXG and 4 NAION eyes. In healthy, PEXG and NAION subjects, scotopic overall mean IPS was 8.90, 3.45 and 4.16 mm 3, and photopic overall mean IPS was 0.87, 0.74 and 1.13 mm 3, respectively. Three‐dimensional contractility showed a mean absolute difference of 8.03 mm 3 for normals (defined as 100% contractility), 2.72 mm 3 for PEXG (33.88% of normal) and 3.03 mm 3 for NAION (38.50% of normal) with a relative light response ratio between scotopic and photopic volumes of 10.26 (100%), 4.69 (45.70%) and 3.67 (35.78%), respectively. Pupillary ejection fraction (PEF) showed a contractile pupillary emptying of 88.11% for normals, 76.92% for PEXG and 70.91% for NAION patients. Conclusion: This 3D pupillometry OCT assessment allows for quantitative measurements of pupil function, contractility and response to light. More specifically, PEF is presented as a potential (neuro)‐pupillary outcome measure that could be useful in the monitoring of ophthalmic disorders that affect pupillary function.